Organizational Commitment Among Kindergarten Teachers (Journal of the College of Basic Education, 2022)
The current research aimed at organizational commitment, among kindergarten teachers. The researcher adopted the (Marzouk 2011) measure of organizational commitment, which amounts to (39) items distributed over four areas (organizational loyalty, desire to continue working, responsibility towards work, belief in the organization). The researcher verified the apparent honesty of the organizational commitment scale and the consistency of its paragraphs, and calculated its stability by re-testing, as it reached the broadcast coefficient (0.94 ) and Cronbach's alpha method, as it reached the reliability coefficient (0.99 ). The researcher applied the two scales to the research sample of (225) kindergarten teachers in Najaf for the year (2021-2022), The sample was chosen in a simple random way, and the research data was processed by statistical means that fit with the nature and objectives of the current research. Among these methods are:Median , Standard Deviation Pearson Correlation Coefficient Cronbach's alphaT-testT-test for a Single Sample T-test for a Correlation Coefficient The researcher reached the following results:The kindergarten teachers have organizational commitment, as they came with an arithmetic mean higher than the hypothetical average.